A method developed to calculate lateral earth pressure on a sheet pile wall with counterforts - Slobodianyk, Anna (Eastern-European Journal of Enterprise Technologies, 2018)
A method has been developed for calculating the lateral earth pressure on a sheet pile wall with counterforts of various shapes – rectangular, trapezoidal with downward expansion, and trapezoidal with upward expansion. Moreover, in the design scheme, two characteristic areas are distinguished along the height of the wall – with and without a counterfort. As a result of considering the equilibrium conditions for elementary volume, equations for determining the lateral earth pressure along the height of the wall have been obtained in the considered sections. The study has produced a mathematical modeling of the system “a sheet pile wall with counterforts plus the soil environment”. Diagrams of the lateral earth pressure are considered for a sheet pile with counterforts. A quantitative evaluation of the relief action of counterforts of various shapes has been obtained. The conducted tests show that the use of counterforts in a sheet pile wall with the considered parameters reduces the pressure of the filling soil to 26 % due to the friction forces along the lateral surface of the counterforts. The introduction of the developed calculation method into engineering practice will allow designing hydraulic engineering structures such as a sheet pile wall with various shapes of counterforts. This will enable the construction of new deepwater hydraulic structures with an increased bearing capacity.